Implementation of RC4 Stream Cipher for Data Security in Internet Café Billing Systems - Marbun, Nasib (Bahasa Indonesia, 2025)
In the field of data communication, cryptography plays a crucial role in ensuring data confidentiality, authenticity, and integrity. This technique is essential when transmitting sensitive information over public networks, preventing unauthorized access or manipulation. In the context of internet cafés (warnet), which provide global computer network access, a secure billing system is vital to prevent data tampering related to user activity duration and associated charges. This study applies the RC4 stream cipher encryption algorithm to protect the billing data. By encrypting user data before storage, the system ensures its confidentiality and integrity. The implementation, developed using Visual Basic 6.0, demonstrates that the encrypted data (ciphertext) maintains a consistent structure with the plaintext, indicating effective encryption without increasing data size. This solution enhances security in internet café billing systems.